The Relationship Of Academic Guidance By Lecturers To Nursing Student’s Burnout Syndrome - Pratiwi Yuliansari; Nugrahaeni Firdausi (Universitas STRADA Indonesia, 2021)
This study aims to determine the relationship between academic guidance by lecturers and nursing students' burnout syndrome. The type of this study was descriptive correlational with cross sectional approach involved 79 respondents selected by total sampling of nursing students who have passed the clinical practice period. The research data then analyzed with linear regression test with a significance level of p <0.05.The study found the significance value of academic guidance with burnout syndrome of nursing students is p = 0.000 with 76 % chance of influence. Intensive academic guidance by lecturers needed to determine the academic and psychological conditions of students in nursing education greatly helps students to be more resilient and regain optimism in completing the study period so as to reduce the burnout syndrome of nursing students